A small-molecule probe for monitoring binding to prolyl hydroxylase domain 2 by fluorescence polarisation - Li, Z; Zhen, S; Anthony, T; Quanwei, Y; Dong, Y; McDonough, M; Schofield, C; Zhang, X (Royal Society of Chemistry, 2020)
Inhibition of the dioxygen sensing hypoxia-inducible factor prolyl hydroxylases has potential therapeutic benefit for treatment of diseases, including anaemia. We describe the discovery of a small-molecule probe useful for monitoring binding to human prolyl hydroxylase domain 2 (PHD2) via fluorescence polarisation. The assay is suitable for high-throughput screening of PHD inhibitors with both weak and strong affinities, as shown by work with clinically used inhibitors and naturally occurring PHD inhibitors.